Inhibition of Clinical MRSA Isolates by Coagulase Negative Staphylococci of Human Origin - Ellen Twomey; Paula M. O'Connor; Aidan Coffey; Maija Kiste; Caitriona M. Guinane; Colin Hill; Des Field; Máire Begley (MDPI AG, 2024)
Staphylococcus aureus is frequently highlighted as a priority for novel drug research due to its pathogenicity and ability to develop antibiotic resistance. Coagulase-negative staphylococci (CoNS) are resident flora of the skin and nares. Previous studies have confirmed their ability to kill and prevent colonization by S. aureus through the production of bioactive substances. This study screened a bank of 37 CoNS for their ability to inhibit the growth of methicillin-resistant S. aureus (MRSA). Deferred antagonism assays, growth curves, and antibiofilm testing performed with the cell-free supernatant derived from overnight CoNS cultures indicated antimicrobial and antibiofilm effects against MRSA indicators. Whole genome sequencing and BAGEL4 analysis of 11 CoNS isolates shortlisted for the inhibitory effects they displayed against MRSA led to the identification of two strains possessing complete putative bacteriocin operons. The operons were predicted to encode a nukacin variant and a novel epilancin variant. From this point, strains Staphylococcus hominis C14 and Staphylococcus epidermidis C33 became the focus of the investigation. Through HPLC, a peptide identical to previously characterized nukacin KQU-131 and a novel epilancin variant were isolated from cultures of C14 and C33, respectively. Mass spectrometry confirmed the presence of each peptide in the active fractions. Spot-on-lawn assays demonstrated both bacteriocins could inhibit the growth of an MRSA indicator. The identification of natural products with clinically relevant activity is important in today's climate of escalating antimicrobial resistance and a depleting antibiotic pipeline. These findings also highlight the prospective role CoNS may play as a source of bioactive substances with activity against critical pathogens.